Design for intercultural education: a cross-disciplinary and heuristic methodology between design, anthropology and pedagogy - Valentina Frosini (Educazione Interculturale, 2022)
Three years after my PhD, I reflect on my action-research based on a preschool in Reggio Emilia and aimed at verifying the design contribution to intercultural education. The paper presents the undertaken process to achieve a cross-disciplinary methodology resulting from a continuous dialogue across the three disciplines – design, anthropology and pedagogy. The paper showcases the research commitment in overcoming disciplinary barriers in order to achieve a meaningful final output, highlighting the new mental habit and project attitude that arose from the research experience. The conclusion part briefly highlights the new role of a designer approaching such challenging times.